Advancing bioinformatics capacity through Nextflow and nf-core: lessons from an early-to mid-career researchers–focused program at The Kids Research Institute Australia - Agudelo-Romero, Patricia; Conradie, Talya; Caparros-Martin, Jose Antonio; Martino, David Jimmy; Kicic, Anthony; Stick, Stephen Michael; Hakkaart, Christopher; Sharma, Abhinav; , the Theme Collaboration Group (Frontiers in Bioinformatics, 2025)
The increasing adoption of high-throughput “omics” technologies has heightened the demand for standardized, scalable, and reproducible bioinformatics workflows. Nextflow and nf-core provide a robust framework for researchers, particularly early- and mid-career researchers (EMCRs), to navigate complex data analysis. At The Kids Research Institute Australia, we implemented a structured approach to bioinformatics capacity building using these tools. This perspective presents nine practical rules derived from lessons learnt, which facilitated the successful adoption of Nextflow and nf-core, addressing implementation challenges, knowledge gaps, resource allocation, and community support. Our experience serves as a guide for institutions aiming to establish sustainable bioinformatics capabilities and empower EMCRs.